Fillers in Mark Zuckerberg’s Interview on Cleo Abram’s Podcast - Aditya Diaz Ilyasa; Widhiyanto Widhiyanto (Journal of English Language Teaching, Linguistics, and Literature Studies, 2026)
This study analyzes a 48-minute podcast episode on Cleo Abram's YouTube channel featuring Mark Zuckerberg, aiming to reveal the types of fillers used and their functions in the context of informal digital communication featuring a technology industry figure discussing complex technological topics. A descriptive qualitative approach supported by simple quantification was employed, using Rose's (1998) and Stenström's (1994) frameworks for analysis. Repeated coding was conducted to ensure intra-rater reliability. "Um" is the dominant unlexicalized filler, while repetition of words or phrases is the most dominant lexicalized filler. The most dominant functions are hesitation and time- creating. The results indicate that fillers function to maintain speech fluency and help the speaker manage cognitive load when conveying complex ideas. It was also found that filler clusters, such as "I mean, um, you know", indicate the cognitive load borne by the speaker. The result indicate that fillers not only act as indicators of speech disruption but also fulfill a significant role in structuring discourse, sustaining interaction, and facilitating communication. From a theoretical perspective, this study enriches the field of pragmatics by broadening the comprehension of filler usage in informal digital communication settings involving figures from the technology industry; a context that has not been thoroughly explored in prior studies. From an educational standpoint, it is essential to recognize fillers as inherent elements of discourse that can assist learners in navigating uncertainties and enhancing their verbal fluency.Keywords: fillers, podcast, spoken communication